Wissenskulturen in der Leibniz-Zeit Konzepte – Praktiken – Vermittlung - Internationaler Leibniz-Kongress; Beiderbeck, Friedrich; Gantet, Claire 1967- (Cultures and practices of knowledge in history, 2021)
How was knowledge produced by different people in different times and at different places? How was knowledge stored, managed, classified, organized, deployed, forgotten, and recycled? Finally, how did such practices affect what counted as knowledge? The series invites contributions on the 'long' early modern period in Europe and publishes also works on global cultures of knowledge under European influence.